Effects of physical activity on children's growth - João Guilherme Bezerra Alves; Guilherme Victor Alves (Elsevier, 2019)
Objective: To describe the current scientific knowledge on the effects of physical exercise on the growth of children and adolescents since intrauterine life. Source of data: A search was carried out in the Medline, Embase, Scielo, and Cochrane databases of studies published from 1990 to 2018. The authors included studies with different designs: clinical trials, cohort, cross-sectional and review studies. Synthesis of data: Studies that addressed the subject of physical exercise or physical activity, and weight-height growth or bone or muscle tissue growth were identified. These studies were analyzed, classified, and presented by age group: fetuses, preterm newborns, preschoolers, schoolchildren, and adolescents. It was observed that almost all studies indicated the safety of physical exercises, of mild to moderate intensity, for pregnant women, as well as children and adolescents, including both aerobic and anaerobic exercises. The retrieve studies did not demonstrate that the practice of physical exercises or certain sports, especially basketball and floor gymnastics, influenced the linear growth of children or adolescents. Some studies showed an increase in bone and muscle tissue growth in child and adolescent athletes. Conclusions: Despite the small number of studies with adequate methodology, especially randomized clinical trials, evidence appears to indicate that physical exercise is safe for both the pregnant woman and the child, from fetal life to adolescence. Physical exercise does not appear to impair the child's linear growth and contributes to the ideal shaping of bone and muscle tissues, ensuring possible beneficial effects throughout life. Resumo: Objetivo: Descrever o conhecimento científico atual sobre os efeitos do exercício físico no crescimento das crianças e adolescentes desde a vida intrauterina. Fonte dos dados: Pesquisa nas bases de dados, Medline, Embase, Scielo e Cochrane que envolveu estudos publicados desde 1990 até 2018. Foram incluídos estudos com diferentes desenhos: ensaios clínicos, coorte, transversais e revisões. Síntese dos dados: Foram identificados estudos que abordaram o tema, exercício físico ou atividade física e crescimento pondero-estatural ou dos tecidos ósseo ou muscular. Os estudos foram analisados, classificados e apresentados por faixa etária: fetos, recém-nascidos pré-termos, pré-escolares, escolares e adolescentes. Observou-se que quase todos todos os apontaram para a segurança do exercício físico de leve a moderada intensidade, tanto para a gestante como para a criança e o adolescente, inclusive tanto os exercícios aeróbicos como os anaeróbicos. Os estudos identificados não comprovaram que a prática de exercícios físicos ou determinados esportes, em especial o basquete e a ginástica de solo, exerciam influência no crescimento linear das crianças ou adolescentes. Alguns estudos demonstraram um maior crescimento do tecido ósseo e muscular em crianças e adolescentes atletas. Conclusões: Apesar do pequeno número de estudos com metodologia adequada, em especial ensaios clínicos randomizados, as evidências parecem indicar que o exercício físico seja seguro, tanto para a gestante como para a criança, desde a vida fetal até adolescência. O exercício físico não parece comprometer o crescimento linear da criança e contribui para moldar de forma ideal os tecidos ósseo e muscular e assegurar possíveis efeitos benéficos ao longo da vida. Keywords: Physical activity, Physical exercise, Growth, Child, Adolescent, Palavras-chave: Atividade física, Exercício físico, Crescimento, Criança, Adolescente